SwoHp, a Nucleoside Diphosphate Kinase, Is Essential in Aspergillus nidulans - Lin, Xiaorong (American Society for Microbiology (ASM), 2003)
The temperature-sensitive swoH1 mutant of Aspergillus nidulans was previously identified in a screen for mutants with defects in polar growth. In the present work, we found that the swoH1 mutant swelled, lysed, and did not produce conidia during extended incubation at the restrictive temperature. When shifted from the permissive to the restrictive temperature, swoH1 showed the temperature-sensitive swelling phenotype only after 8 h at the higher temperature. The swoH gene was mapped to chromosome II and cloned by complementation of the temperature-sensitive phenotype. The sequence showed that swoH encodes a homologue of nucleoside diphosphate kinases (NDKs) from other organisms. Deletion experiments showed that the swoH gene is essential. A hemagglutinin-SwoHp fusion complemented the mutant phenotype, and the purified fusion protein possessed phosphate transferase activity in thin-layer chromatography assays. Sequencing of the mutant allele showed a predicted V83F change. Structural modeling suggested that the swoH1 mutation would lead to perturbation of the NDK active site. Crude cell extracts from the swoH1 mutant grown at the permissive temperature had ∼20% of the NDK activity seen in the wild type and did not show any decrease in activity when assayed at higher temperatures. Though the data are not conclusive, the lack of temperature-sensitive NDK activity in the swoH1 mutant raises the intriguing possibility that the SwoH NDK is required for growth at elevated temperatures rather than for polarity maintenance.